Signet Ring Cell Carcinoma of the Breast: About A Case and Literature Review - Acharfi, Nisrine; Boujarnija, Raihana; Messoudi, Kaouthar; Darif, Khadija; Ouahbi, Hajar; Ouafki, Imane; Amaadour, Lamiae; Oualla, Karima; Benbrahim, Zineb; Arifi, Samia; Douida, Amal; Fatemi, Hind EL; et al. (International Journal of Innovative Research in Medical Science, 2020)
Singnet ring cell carcinoma of the breast is a rare and aggressive tumor. We report the case of a 44-year-old woman with signet ring cell carcinoma of breast who was treated in the gynecology and medical oncology departments of HASSAN II Hospital University in Fez. She received a neoadjuvant chemotherapy with the anthracyclines and taxanes. After she had radical mastectomy and radiotherapy. Currently she has remained in good control.